Climate change, double injustice and social policy: A case study of the United Kingdom - Ian Gough (United Nations Research Institute for Social Development (UNRISD), 2011)
The groups and populations likely to be most harmed by climate change are the least responsible for causing it and have the least resources to cope with the consequences-this is the "double injustice". It forms the background to climate negotiations between governments representing countries of the North and the South, but it also occurs within nations across the world. In light of this phenomenon, what are the distributional implications of current, fairly ambitious, policies to decarbonize the economy? Based on research within rich countries of the Organisation for Economic Development and Co-operation (OECD), and building specifically on UK studies and data, this question is answered in two parts: within the Kyoto framework and beyond it. This paper complements the author's Report for the British Council on Climate Change and Public Policy Futures. The United Kingdom is legally committed to reduce emissions of greenhouse gases by 80 per cent by 2050, compared with the base year of 1990. The European Union has similar collective commitments. These drastic targets are to be implemented via a wide range of carbon mitigation policies (CMPs). This paper considers the social dimension and distributive implications of these policies, and how these might be tackled. First, the paper finds that many CMPs in the United Kingdom are highly regressive, notably those where energy companies are "obliged" by government to improve energy efficiency and increase renewable energy, the costs to be met by increasing energy prices for domestic and business users. Since energy is a basic good, it comprises a far higher share of spending in lower income households; thus such cost hikes are regressive. CMPs bear more heavily on poorer households. It is impossible to fully recompense lower income households for these cost increases via social benefits, tax allowances and credits because of the heterogeneity of their circumstances and their dwellings...
Keywords: 330